RELATIONSHIP OF NEUTROPHIL LYMPHOCYTE RATIO WITH APPENDICITIS INCIDENCE Review of Appendicitis Patients at Ibnu Sina Hospital, Gresik Regency in 2022-2023 - Rahman, Akhmad Setyo; Harijanto, Taufan; Marsetio, Dono; Negara, Agung Kusuma; Fadhilah, Nur Lailatul (NUCLEUS, 2024)
This study aims to analyze the relationship between the neutrophil lymphocyte ratio (NLR) and the incidence of acute appendicitis in patients at Ibnu Sina Hospital, Gresik Regency, in the 2022-2023 period. Acute appendicitis is a frequent emergency surgical condition, especially in adolescents and young adults, with the risk of complications such as perforation and peritonitis. NLR, as an indicator of inflammatory response, is considered more practical and economical than CT scans and ultrasounds, which have limited cost, accessibility, and risk of radiation exposure. This study used an observational analytical method with a cross-sectional approach on 51 appendicitis patients who underwent appendectomy. NLR data was obtained through routine blood results, with statistical analysis using SPSS to test the normality and difference in NLR values between uncomplicated appendicitis and appendicitis with complications. There was a significant difference in the mean NLR value between patients with complementary and non-complementary appendicitis, with a p < value of 0.001. The results of the ROC Curve analysis show that NLR has a high prediction value in predicting complementary appendicitis of 97.5%. This study concludes that NLR can be an effective indicator in distinguishing cases of complementary and non-complementary appendicitis and the potential of NLR as an easy and efficient screening tool in the treatment of acute appendicitis, especially in health facilities with limited resources.